ON SEISMICSENSITIVITY OF BIOSYSTEMS AND COSMIC CYCLE PERTURBATION: ON SEISMICSENSITIVITY OF BIOSYSTEMS AND COSMIC CYCLE PERTURBATION - Adeishvili, Teimuraz; Aleksandrov, Aleksandar; Jikia, Magdana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper discusses the connections of the occurrences in biosphere with the cosmic seismic activity and cosmic cycles, namely, with the interposition of the sun and the planets. Some relation patterns between the changes of the radon concentration in thermal-mineral waters, the physiological events occurring in and biosystem and cosmic biorhythms have been revealed.